The river murders [large type] : thrillers - Patterson, James, 1947-; Born, James O. ([Mitchum series, 2020)
Hidden: "After being rejected by the Navy SEALS, Mitchum becomes his small town's unofficial private eye. But his investigation skills are put to the test when he searches for his missing teenage cousin - and uncovers a government conspiracy in the process"--Provided by publisher.